Pengenalan Lean Manufacturing untuk Meningkatkan Daya Saing UKM Rendang Gadih di Payakumbuh - Fahlevi, Fidruzal; Amrina, Elita; Hasan, Alizar; Putri, Nilda Tri; Zadry, Hilma Raimona; Indrapriyatna, Ahmad Syafruddin; Taufik; Wirdianto, Eri; Kamil, Insannul; Fithri, Prima; Wisnel; Rahmayanti, Dina; Jumeno, Desto; Patrisina, Reinny; Adi, Alexie Herryandie Bronto; Huda, Ashila Nurul; Liperda, Rahmad Inca; Fandeli, Hary; Maulana, Ghufran; Febriano, Raihan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Small and Medium Enterprises (SMEs) are the backbone of Indonesia's economy, contributing over 60% to the national GDP and employing more than 97% of the workforce. In Payakumbuh, culinary SMEs have significant potential due to the abundance of local raw materials and high demand for traditional foods such as rendang. Rendang Gadih is one such SME focusing on rendang production for both local and regional markets. However, inefficiencies in production, inconsistent quality, and manual management processes limit its competitiveness. This community service activity introduced the concept of Lean Manufacturing to improve efficiency and reduce waste. The main tools socialized were Value Stream Mapping (VSM), Process Activity Mapping (PAM), and identification of the eight types of waste, along with the application of Kaizen principles for continuous improvement. Implementation was carried out through preparation, socialization, and evaluation stages. The results of this activity are expected to help Randang Gadih enhance production efficiency, minimize waste, and strengthen competitiveness, serving as a model for other culinary SMEs in West Sumatra.